Prevod na pogled (prima vista) - od popestritve klasičnega pouka prevajanja do lakmusovega papirja za prevajalske probleme - Rieger, Mladen (Vestnik za tuje jezike, 2014)
When students first become acquainted with translating, especially into non-mother tongue, the gap between the known and the unknown is large, demanding different approaches, adapted progress and the setting of narrower didactic objectives which enable the development of translation competences as well as ensure the linguistic admissability of translations, but at the same time do not turn the exercises in translation into linguistic studies. Our survey which combined the well-established empirical method of the think-aloud protocol and the method of the prima vista translation aimed to examine how students find their way around translating culturally specific texts into their mother and non-mother tongue, whether they take into account the results of the textual analysis and how they put the translation order into practice. The analysis has shown that the tested persons managed to adequately identify the culturally specific elements and found culturally acceptable equivalents, but they produced functionally unacceptable translations due to the insufficient or left-out translation-targeted textual analysis.
Keywords: prevajanje; translation; prevod na pogled; protokol glasnega razmišljanja; analiza besedila; kulturne posebnosti; univerzitetni študij